Vid : Lobesia botrana Den et Schiff. (pollilla europea del racimo) - Becerra, Violeta Cristina; Herrera, Maria Eugenia; Gonzalez, Marcela Fabiana; Mendoza, Graciela Beatriz; Dagatti, Carla Vanina (2017)
EEA Alto Valle